Pengaruh Kualitas Produk dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Viva Cosmetics di Kabupaten Banyumas - Milla Azizah (SMARTINDO, 2025)
The purpose of this study was to determine the analysis of the influence of product quality and customer satisfaction on customer loyalty of Viva Cosmetics beauty products. The objects of this study are product quality, customer satisfaction and customer loyalty. While the subjects of this study were the Banyumas community who use Viva Cosmetics products. The respondents in this study numbered 99 people. The sampling technique used was purposive sampling. Respondents who met the requirements for this study were the Banyumas Regency community who were loyal to Viva cosmetics. Data were collected using a questionnaire. The analysis method used was multiple regression analysis, which previously had its research instrument tested with validity and reliability tests. The results of the analysis proved that all variables were declared valid and reliable so that they could be used for research, and all classical assumptions were met. The hypothesis test conducted proved that product quality and customer satisfaction partially and simultaneously had a significant effect on customer loyalty of Viva Cosmetics in Banyumas Regency.